2014
DOI: 10.1149/2.071405jes
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol Salt Particle Deposition on Metals Exposed to Marine Environments: A Study Related to Marine Atmospheric Corrosion

Abstract: The characterization and corrosive effect of marine salt particles and seawater droplets that naturally deposited onto carbon steel and pure zinc that were exposed to marine test sites were studied. Most of the salt particles had diameters ranging from approximately 2-10 μm, and varied in their composition ranging from almost pure NaCl or KCl to mixtures of NaCl, KCl, CaCl 2 , and MgCl 2 . The differences in composition may depend on whether the seawater droplets dehydrate, crystallize, and fragment while airb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 63 publications
0
22
0
Order By: Relevance
“…In marine site with high amount of chloride deposition, β-FeOOH is produced as for chloride accelerative effect, while the main corrosion products are γ-FeOOH and α-FeOOH in exposure station with low or no chloride. Chloride mainly comes from the ocean and deicing (ISO, 2012a).The deposition rate of chloride from the ocean is affected by wind speed and wind direction (Cole et al 2003b;Li and Hihara 2014;Roberge et al 2002), distance from the coast (Cole et al 2003b;Cole et al 2003a;Guerra et al 2019), rainfall (Cole et al 2004a), temperature and humidity (Castaneda et al 2018;Cole et al 2003b), terrain (Cole et al 2003c;Cole et al 2004a) and other factors (Cole et al 2011). The influence of chloride has a significant relationship with the distance from the sea (Abbott 2008;Feliu et al 1999).…”
Section: Influence Of Pollutantsmentioning
confidence: 99%
See 1 more Smart Citation
“…In marine site with high amount of chloride deposition, β-FeOOH is produced as for chloride accelerative effect, while the main corrosion products are γ-FeOOH and α-FeOOH in exposure station with low or no chloride. Chloride mainly comes from the ocean and deicing (ISO, 2012a).The deposition rate of chloride from the ocean is affected by wind speed and wind direction (Cole et al 2003b;Li and Hihara 2014;Roberge et al 2002), distance from the coast (Cole et al 2003b;Cole et al 2003a;Guerra et al 2019), rainfall (Cole et al 2004a), temperature and humidity (Castaneda et al 2018;Cole et al 2003b), terrain (Cole et al 2003c;Cole et al 2004a) and other factors (Cole et al 2011). The influence of chloride has a significant relationship with the distance from the sea (Abbott 2008;Feliu et al 1999).…”
Section: Influence Of Pollutantsmentioning
confidence: 99%
“…The types, size and distribution of aerosols can influence the initiation and propagation of the corrosion process in more complex ways (Li and Hihara 2014;Risteen et al 2014). Take zinc as an example, the presence of acidified aerosols may lead to enhanced corrosion by disrupting any protective oxide films and subsequently establishing electrochemical cells, relatively uniform oxide layers are formed, which may be dissolved by typical aerosol with pH values of 1-4 and slightly acidified rain (<5) (Azmat et al 2011) and thus may not constitute as an effective barrier against corrosion.…”
Section: Influence Of Pollutantsmentioning
confidence: 99%
“…[1][2][3][4][5] The high corrosion rates in marine environments greatly reduce the lifetime of steel structures. Therefore, a better understanding of the corrosion mechanisms of steel is necessary for evaluating the performance and developing corrosion-control strategies.…”
mentioning
confidence: 99%
“…Li et al [ 21 ] looked at salt deposition and corrosion for very short exposure times (30 min) in a marine Hawaiian locations on low carbon steel and zinc. In this, they duplicated the earlier test of Cole et al [ 22 ] in Australia with very similar results.…”
Section: Oxide Formationmentioning
confidence: 99%
“…In this, they duplicated the earlier test of Cole et al [ 22 ] in Australia with very similar results. Li et al [ 21 ] found that the corroded region or the original droplet was from 10–30 µm. Corrosion occurred at all sizes and secondary spreading was observed for the larger droplets.…”
Section: Oxide Formationmentioning
confidence: 99%